2015
DOI: 10.1093/jxb/erv313
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific lipid transfer proteins in plants: presenting new advances and an integrated functional analysis

Abstract: Plant non-specific lipid-transfer proteins (nsLTPs) are small, basic proteins present in abundance in higher plants. They are involved in key processes of plant cytology, such as the stablization of membranes, cell wall organization, and signal transduction. nsLTPs are also known to play important roles in resistance to biotic and abiotic stress, and in plant growth and development, such as sexual reproduction, seed development and germination. The structures of plant nsLTPs contain an eight-cysteine residue c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
213
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(221 citation statements)
references
References 198 publications
7
213
0
1
Order By: Relevance
“…Beyond the nutrient reservoir function, the observed protein profile includes many GTPases involved in vesicle trafficking, cytoskeletal organisation and signal transduction as recently confirmed in peach by another paper (Falchi, Cipriani, Marrazzo, Nonis, Vizzotto, & Ruperti, 2010). We have identified also phosphatidylinositol binding protein, an important lipid binding proteins, playing roles in the stabilisation of membranes, cell wall organisation, seed development and germination (Liu, Zhang, Lu, Zeng, Li, Fu, et al, 2015). In addition, some methyltransferases were recognised.…”
Section: Glycine Max Vitis Vinifera Zea Mays and Populus Trichocarpasupporting
confidence: 68%
“…Beyond the nutrient reservoir function, the observed protein profile includes many GTPases involved in vesicle trafficking, cytoskeletal organisation and signal transduction as recently confirmed in peach by another paper (Falchi, Cipriani, Marrazzo, Nonis, Vizzotto, & Ruperti, 2010). We have identified also phosphatidylinositol binding protein, an important lipid binding proteins, playing roles in the stabilisation of membranes, cell wall organisation, seed development and germination (Liu, Zhang, Lu, Zeng, Li, Fu, et al, 2015). In addition, some methyltransferases were recognised.…”
Section: Glycine Max Vitis Vinifera Zea Mays and Populus Trichocarpasupporting
confidence: 68%
“…LTPs in maize (ZmLTPs) have critical roles in resistance to biotic and abiotic stress. They provide high salinity resistance with decreasing solute permeability of cell membrane (Liu et al 2015). 63 nsLTP genes identifi ed and differentially expressed under drought, salt and cold stresses were unevenly assigned to ten maize chromosomes by in silico mapping (Wei and Zhong 2014).…”
Section: Discussionmentioning
confidence: 99%
“…LTPs are in general coded by several genes that belong to a multigene family, as demonstrated in Arabidopsis and rice (Liu et al, 2015). The results of immunohistochemistry in seed tissue compared with histochemistry showed that LTPs and lipids were present in the same tissues.…”
Section: Discussionmentioning
confidence: 92%